Як довгi неправильнi пуриново-пуриновi пари основ днк набувають ензиматично-компетентної конформацiї? Структурний механiзм тайогоквантово-механiчнеобґрунтування - Brovarets, O. O.; Hovorun, D. M. (Publishing house "Academperiodika", 2019)
Aimed at the answer the biophysically important question posed in the title of this article, we have first investigated, at the MP2/aug-cc-pVDZ//B3LYP/6-311++G(d,p) level of quantum-mechanical theory, the structural, energetic, and dynamic features of the acquisition of the enzymatically competent conformation by the incorrect А*·А(WC), G·A(WC), A*·G*(WC), and G*·G(WC) DNA base mispairs with the Watson–Crick (WC) geometry – active players on the field of spontaneous point mutagenesis. It is first shown that the characteristic time of these non-dissociative A*·A(WC)↔A*·Asyn(TF), G·A(WC)↔G·Asyn, A*·G*(WC)↔A*·G*syn, and G·G*(WC)↔G·G*syn conformational transitions is much less than the period of time that it is spent by a high-fidelity DNA-polymerase on the incorporation of one nucleotide into the DNA double helix.